THE INFLUENCE OF PROFITABILITY AND LIQUIDITY TOWARDS STOCK PRICE (EMPIRICAL STUDY ON PROPERTY SECTOR SERVICE COMPANIES LISTED ON IDX FOR THE PERIOD 2018-2020) - Christine, Debbie; Muhammad, Satria Giri; Kristopan, Kevin; Utama, Dega Hesa Putera; Alamien, Mohammad Rifada Yasara; Firdaus, Mohammad Avicenna (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study is to examine and analyze the influence of Profitability (ROA) and Liquidity (CR) on the stock prices of property sector service companies listed on the Indonesian Stock Exchange between 2018 and 2020. This research method is descriptive in nature. The population for this study is property sector service companies listed on IDX between 2018 and 2020, totaling 48 companies. A purposive sampling technique was used to obtain a total of 25 samples of companies. The analysis technique used is the panel data model test, the classical assumption test, and hypothesis testing with the t-statistical hypothesis test for partial regression coefficients and the F-statistical hypothesis test for simultaneous regression coefficients with a significance level of 5%. The results indicate that profitability and liquidity have an influence on stock prices in property sector service companies listed on IDX between 2018 and 2020, while profitability influenced stock price and liquidity had no influenced on stock price.